Statistical Modeling of Youth Unemployment and School Non-attendance in Pattani and Songkla Province of Thailand - Sunaree, Suwanro (Prince of Songkla University, 2012)
Thesis (Ph.D.(Research Methodology))--Prince of Songkla University, 2011